Institucionalização das políticas de promoção da igualdade racial no Brasil: percursos e estratégias 1986 a 2010 - Ribeiro, Matilde (2013)
This thesis aims to analyze the trajectories and strategies for the institutionalization of racial equality policies in Brazil from 1986 to 2010, considering that in recent decades the Black Movement and the organization of black women have constituted strategic references for confrontation and negotiation with the State and society with a view to attending to the historical needs of the black population. The research was based on critical theory, using authors from several fields social work, sociology, politics, philosophy, history, anthropology, social psychology, economics, law, education and race relations. The methodological procedures adopted were bibliographical and documentary research, as well as field work with an emphasis on participant observation. The Brazilian literature was amply consulted, in addition to international references conference declarations and reports, legislation, regulations, speeches by Presidents of the Republic, governmental programs and projects, as well as the theoretical/political production of the social movement. Twenty-one interviews were conducted with eight women and thirteen men, of whom four white and seventeen black with people with activities in various fields: social movements (Black Movement, black women s organizations, feminist movement, labor movement), academia and the Legislative and Executive branches at the federal level. The theoretical and empirical analyses show that during the period studied, governments have recognized the existence of racism and the need to overcome it. Hence, one has witnessed the institutionalization of public policies of racial equality promotion, in the form of affirmative actions. But this institutionalization has not yet become consolidated. There remain numerous structural and budgetary difficulties, as well as strong conflicts between more progressive and traditional views on race relations in Brazil, the latter based on the myth of racial democracy. However, the study does identify certain social and political changes that reveal greater advances in terms of rights vis-à-vis the promotion of socio-racial justice